Going to Teach and Getting Taught in Saudi Arabia: An Auto-Ethnography - Michelle Glowacki-Dudka (Adult Education Research Conference, 2007)
This study examines cultural consequences of working in Saudi Arabia. Findings demonstrate that absence of preliminary understanding of cultural differences may adversely impact relationships, both personal and professional.